Pengaruh Biaya Kualitas Terhadap Produk Rusak pada PT Faninda Jaya Meubel Kabupaten Gorontalo - Hasanuddin Hasanuddin; Dewi Sartika; Muhammad Anas; Hariatih Hariatih (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2021)
The analytical method used in this study is path analysis with independent variables: prevention costs (X1), appraisal costs (X2), internal failure costs (X3), external failure costs (X4) and the dependent variable is defective products (Y). This study aims to determine how much influence the cost of quality includes: prevention costs, appraisal costs, internal failure costs, external failure costs to damaged products, both simultaneous and partial effects. By using a sample of 81 employee respondents. The results showed that the cost of quality partially consisting of the variable cost of prevention (X1) had a positive and significant effect on damaged products by 44.3%, the variable cost of assessment (X2) had a positive and significant effect on damaged products by 24.4%. internal failure costs (X3) have a positive and significant effect of 22.1% and external failure costs have a positive and significant effect on damaged products by 31.3% and the simultaneous effects include prevention costs (X1), appraisal costs (X2) , internal failure costs (X3) and external failure costs (X4) positively and significantly on damaged products at PT. Faninda Jaya Furniture is 54.7% while 45.3% is influenced by other variables not examined